2002
DOI: 10.1152/ajpgi.00310.2001
|View full text |Cite
|
Sign up to set email alerts
|

Expression of monosaccharide transporters in intestine of diabetic humans

Abstract: Noninsulin-dependent diabetes mellitus (NIDDM) is an increasingly common disease, which brings a number of life-threatening complications. In rats with experimentally induced diabetes, there is an increase in the capacity of the intestine to absorb monosaccharides. We have examined the activity and the expression of monosaccharide transporters in the intestine of patients suffering from NIDDM. Na(+)-dependent D-glucose transport was 3.3-fold higher in brush-border membrane (BBM) vesicles isolated from duodenal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
212
4
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(229 citation statements)
references
References 40 publications
11
212
4
2
Order By: Relevance
“…Substrate availability has been shown to affect hexose transporter expression in intestinal epithelial cells but has not been directly evaluated in muscle. Hyperglycemia directly increases intestinal glucose absorption severalfold (21). Dyer et al (21) demonstrated threefold increased transport of D-glucose into brush-border membrane vesicles isolated from duodenal biopsies of patients with type 2 diabetes.…”
Section: Impact Of the 8-week Protocol On Glycemic Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Substrate availability has been shown to affect hexose transporter expression in intestinal epithelial cells but has not been directly evaluated in muscle. Hyperglycemia directly increases intestinal glucose absorption severalfold (21). Dyer et al (21) demonstrated threefold increased transport of D-glucose into brush-border membrane vesicles isolated from duodenal biopsies of patients with type 2 diabetes.…”
Section: Impact Of the 8-week Protocol On Glycemic Controlmentioning
confidence: 99%
“…Dyer's group hospitalized several patients with diabetes and intensively managed their blood glucose levels. They found that the overexpression of GLUT5 and SGLT1 in the intestinal epithelium returned to normal (21), suggesting that hyperglycemia had played a role in the overexpression of the transporters in the gut of the diabetic subjects.…”
Section: Impact Of the 8-week Protocol On Glycemic Controlmentioning
confidence: 99%
“…This was consistent with dietary upregulation of the GLUT transporters and suggested that GLUT5 is primarily responsible for fructose absorption, but that GLUT2 recruitment to the brush border membrane could be an important adaptation when the intestine is challenged with a large dose of fructose (27). Although GLUT2 has not been confirmed in the brush border membrane for humans, the biopsy samples were obtained from patients who were fasted (18) or deceased (5). These findings suggest that GLUT2 is not constitutively located on the brush border membrane of the human small intestine, but it could be transiently upregulated by glucose, as observed in a murine model.…”
Section: Transport Of Fructosementioning
confidence: 67%
“…Dyer et al (41) have reported that brush border Na + / glucose cotransport SGLT1 mRNA and protein levels in duodenal biopsies are 3-to 4-fold higher in diabetic subjects than in controls. They have concluded that there is an increased capacity to absorb glucose in diabetic subjects and that this is due to both a rise in transporter expression and structural changes in the brush border membrane.…”
Section: Sglts and Diabetesmentioning
confidence: 99%